Pengaruh Brand Personality terhadap Keputusan Pembelian dan Minat Beli sebagai Variabel Intervening pada Produk Kosmetik Somethinc - rakhmania Hemas Amanah (Program Studi Hubungan Masyarakat Politeknik LP3I, 2022)
ABSTRACT This study aims to determine the effect of Brand Personality on purchasing decisions mediated by buying interest. This type of research uses quantitative methods by distributing questionnaires through google forms. The population used in this research are followers of the SomeThinc Instagram account and have used products from SomeThinc. The sampling technique in this study was using purposive sampling technique with a total sample of 600 respondents. The analysis technique used is the path analysis method. Path analysis results X to Y With variable Z as the intervening variable, it can be concluded that the brand personality variable (X) has a direct effect on the purchase interest variable (Z) of 0.364. then for the purchase interest variable (Z) has a direct effect on the purchasing decision variable (Y) of 0.482. Meanwhile, the Brand personality variable (X) has a direct effect on purchasing decisions (Y) of 0.312 and an indirect effect of 0.306 because it is through the intervening variable that buying interest (Z) so that the total effect is 0.618. Researchers can draw several conclusions including; 1. Brand personality has a significant effect on purchasing decisions, 2. Purchase intention as an intervening variable is not able to mediate the influence of brand personality on purchasing decisions